Trapping for Sirex Woodwasp in Brazilian Pine Plantations: Lure, Trap Type and Height of Deployment - Batista, Elder S. P. [UNESP]; Redak, Richard A.; Busoli, Antonio Carlos [UNESP]; Camargo, Mariane B.; Allison, Jeremy Dean (Springer Nature, 2018)
The Sirex woodwasp, Sirex noctilio (Hymenoptera: Siricidae) is considered a secondary pest of pine in its native range but has caused considerable economic losses in pine plantation forests in the southern hemisphere. In Brazil, trap trees are the primary tool used for early detection purposes but these are costly, labor-intensive to install and require stressing trees by herbicide application. Flight intercept traps baited with synthetic blends of host volatiles are an attractive alternative but have performed poorly in some settings. This study was carried out to look for alternatives to trap trees for use in Brazilian pine plantations for early detection of S. noctilio. Four field experiments were conducted in two consecutive flight seasons (2015–16 and 2016–17), in planted loblolly pine (Pinus taeda) stands, to compare captures among flight intercept traps baited with different lures, deployed at different heights and among different intercept trap designs. Two experiments compared different host volatile lures and a significant treatment effect was observed in one. No effect of trap design or height was observed.
Keywords: European woodwasp; invasive species; survey and detection; woodborer